Identifikasi Risiko Keselamatan dan Kesehatan Kerja (K3) dengan Menggunakan Metode HIRARC di PT. XYZ - Rohman, Abd; Sulistyowati, Enik (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
PT. XYZ is a company operating in the fields of electrical contracting, maintenance services, and the supply of electrical equipment. Activities such as welding and grinding present significant risks of workplace accidents. This report aims to identify and assess these risks using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. The analysis revealed several high-risk hazards, including burns caused by sparks, respiratory problems due to welding fumes, and injuries from grinding debris. To address these risks, PT. XYZ has implemented various control measures such as the use of appropriate Personal Protective Equipment (PPE), the enforcement of Standard Operating Procedures (SOPs) for equipment maintenance, and the provision of occupational safety and health (OSH) training. The application of the HIRARC method has proven effective in systematically managing workplace safety, and it is recommended that the company continue enhancing supervision, safety training, and compliance with established procedures to ensure a safer and more productive work environment.